Mr. Palengke advertisements language as a cultural dimension in the development of a communication campaign using the high and low context cultural framework - Ramiro, Teresa Joselyn V. (2008)
"While there is an enormous amount of literature on the general subject of language as a cultural dimension, very little has been written about how language influences the development of a communication campaign in relation to the High and Low context framework. Thus, this study looks at how language, as a cultural dimension, may influence the development of a communication campaign for a political candidate--particularly Mar Roxas-- and how language becomes important in persuasion as perceived by Filipino voters and the advertising agency and strategists. To be more specific, the discussion evolves on how an advertising agency constructed an image for Mar Roxas as a political condidate in relation to the culture of Filipino voters using the High and Low context framework. It also deals with understanding the dispositions, character of values of Filipino voters in relation to the advertisements of Roxas using the cultural context framework. This study cites the case of "Mr.Palengke" television commercials of Mar Roxas. Accounting for about 60 percent of his media expenditure in the 2004 election, the advertisements serve as case in points. The first ad talks about Mar Roxas as"Mr. Palengke" while the second ad, the "Election ad" or the "political pedigree ad" talks about his image as a Senatorial Candidate in the 2004 National elections. In this study, moreover, the following theories were used: Edward Hall's High and Low Context Framework and the Communication Campaign Model by K.E. Nowak and Karl Warneryd. These theories serve as references for the study drawn from the literature. The researcher used multi-methods in conducting this research. The following research methods were used anmely Focus Group Discussion with One-shot Survey using the Cultural Context Inventory, In-depth Interview, Participant Observation and Textual Analysis. This study shows that the campaign's elements such as the objectives, target audience, strategy, message, communicator, budget and resources are closely interrelated. Thus, when the aim or even the language of a campaign changes, all or some of the other elements in the campaign will change. Furthermore, results show that language is involved in developing a message format- which is verbally related to words, their definitions, use of space, color, music and other sounds, and clothing."
"This research also highlights the importance of language in everyday life. In addition to "what to say", it is important to know "how you say it", as our parents always told us. And, part of the "hoe you say it" is the language one uses. Language shapes behavior is a need to tailor-fit communication to the audience--depending on their classification as High Context or Low Context and depending on their social strata and educational level. In this case, the advertisements of Roxas displayed both High and Low Context characteristics. In general, there are more attributes of high context seen in the ads of Roxas. Thus, the ads are likely to terget people who tend to be in the same context. As discussed in the literature, Asians like Filipinos are likely to be in the high context. On the other hand, the participants in the Focus Group Discussion tend to be in the low context. That is why they are likely to appreciate the Election ad or the "political pedigree ad" because it is simpler, more consistent, and it follows a more logical pattern compares to the Mr. Palengke advertisement. Such characteristics are seen in a Low Context culture. However, this is not a reflection of the entire Filipino population in relation to their tendencies or preferences in the High and Low context continuum. In the context of advertising, advertisers should take note of the differences between various cultures. Advertisers or strategists should be able to develop campaign that will eventually capture their audience because they have a clearer understanding of their market."
Vita.
Thesis (M.A. Communication Research)--University of the Philippines, Diliman.
Keywords: Political campaigns -- Philippines -- Cross-cultural studies; Commnunication in politics -- Philippines -- Cross-cultural studies; Advertising, Political -- Philippines -- Cross-cultural studies; Language